Human resource system as innovation for organisations - Túlio Gomes Mauro; Jairo Eduardo Borges-Andrade (Innovation & Management Review, 2020)
Purpose - This paper aims to identify relevant aspects to achieve advantage of the innovative potential of a human resource information system (HRIS). The present study compared the system implementation professionals' perception of the results expected from the system, its characteristics and how it should be implemented. Design/methodology/approach Semi-structured interviews were conducted with eight information technology specialists and ten human resource (HR) professionals from four organisations at different stages of HRIS implementation, in which two had it fully implemented and two were undergoing the implementation process. The resulting data were submitted to four sets of content analyses and then compared. Findings Findings suggest specificities in the perception of these professionals. Critical aspects regarding the effective adoption of HRIS were addressed, such as characteristics of the systems, implementation process and human resource management model. Originality/value The implementation of an HRIS alone does not ensure the achievement of the obtained advantages. The results of the present study provide guidelines for implementation of HRIS as innovation for a strategic management of people. These guidelines come from different knowledge areas and from different stages of implementation. These findings corroborate models of innovation diffusion and technology acceptance.
Keywords: 650; Human resource information system; Human resources; Innovation; Strategic human resource; System implementation